Highways, byways, and road systems in the pre-modern world - Alcock, Susan E.; Bodel, John P., 1957-; Talbert, Richard J. A., 1947- (New York : Wiley-Blackwell, 2012)
"The unparalleled network of roads in the empire of ancient Rome was a remarkable achievement--yet this Roman road network is just the most notable example of an important feature of many pre-modern societies worldwide. Highways, Byways, and Road Systems in the Pre-Modern World presents a comparative analysis of several sophisticated systems of overland transport and communication networks across pre-modern cultures. Featuring contributions from an international team of scholars, these readings delve deeply into the societal, cultural, and religious implications of various transportation networks around the globe. The latest research from the Mediterranean and the Near East is brought together with fresh work from the Americas, Africa, and Asia to reveal the significance and logistics of the movement of people and ideas in the pre-modern world. Highways, Byways, and Road Systems in the Pre-Modern World sheds important new light--and fills a gap in contemporary scholarship--by exploring the importance and interconnectedness of the countless physical pathways of peoples and cultures"--
Front Matter -- Introduction / Susan E Alcock, John Bodel, Richard J A Talbert -- Overland Shortcuts for the Transmission of Buddhism / Jason Neelis -- The Power of Highway Networks during China's Classical Era (323 316): Regulations, Metaphors, Rituals, and Deities / Michael Nylan -- Privatizing the Network: Private Contributions and Road Infrastructure in Late Imperial China (15001900) / Nanny Kim -- Linking the Realm: The Gokaid̥ Highway Network in Early Modern Japan (16031868) / Constantine N Vaporis -- Obliterated Itineraries: Pueblo Trails, Chaco Roads, and Archaeological Knowledge / James E Snead -- Roads to Ruins: The Role of in Ancient Maya Society / Justine M Shaw -- The Chinchaysuyu Road and the Definition of an Inca Imperial Landscape / Catherine Julien -- The Sahara as Highway for Trade and Knowledge / Pekka Masonen -- From the Indus to the Mediterranean: The Administrative Organization and Logistics of the Great Roads of the Achaemenid Empire / Pierre Briant -- The Well-Remembered Path: Roadways and Cultural Memory in Ptolemaic and Roman Egypt / Jennifer Gates-Foster -- Roads, Integration, Connectivity, and Economic Performance in the Roman Empire / R Bruce Hitchner -- Roads not Featured: A Roman Failure to Communicate? / Richard J A Talbert -- Road Connectivity and the Structure of Ancient Empires: A Case Study from Late Antiquity / Michael Maas, Derek Ruths -- Jews and News: The Interaction of Private and Official Communication-Networks in Jewish History / Adam Silverstein -- Index.
Includes bibliographical references and index.
Keywords: Roads -- Social aspects; Roads -- History; LITERARY CRITICISM -- Ancient & Classical; Business; LITERARY CRITICISM -- Ancient & Classical; BUSINESS & ECONOMICS -- Industries -- Transportation; TRANSPORTATION -- Public Transportation; Roads; Roads -- Social aspects; Wegen; Oudheid; Electronic books; History